The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/advs.202002085
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathological Factors Affecting Drug Delivery to the Brain by Nanoparticles

Abstract: The prevalence of neurological/neurodegenerative diseases, such as Alzheimer's disease is known to be increasing due to an aging population and is anticipated to further grow in the decades ahead. The treatment of brain diseases is challenging partly due to the inaccessibility of therapeutic agents to the brain. An increasingly important observation is that the physiology of the brain alters during many brain diseases, and aging adds even more to the complexity of the disease. There is a notion that the permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 502 publications
(656 reference statements)
0
16
0
Order By: Relevance
“…However, the higher density of ligand could not only decrease the binding ability of nanoparticles to receptors due to steric hindrances caused by too closely adjacent ligands, but also possibly enhance nonspecific interactions in vivo. [ 31 ] Therefore, an optimal ligand density is required to promote sufficient BBB crossing. To optimize the efficiency of BBB penetration, preparations with different α Ang ligand densities of 1%, 5%, 10%, and 15% (corresponding lipids were denoted as 1% APLN/MB, 5% APLN/MB, 10% APLN/MB, and 15% APLN/MB, respectively) were prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the higher density of ligand could not only decrease the binding ability of nanoparticles to receptors due to steric hindrances caused by too closely adjacent ligands, but also possibly enhance nonspecific interactions in vivo. [ 31 ] Therefore, an optimal ligand density is required to promote sufficient BBB crossing. To optimize the efficiency of BBB penetration, preparations with different α Ang ligand densities of 1%, 5%, 10%, and 15% (corresponding lipids were denoted as 1% APLN/MB, 5% APLN/MB, 10% APLN/MB, and 15% APLN/MB, respectively) were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Transmembrane resistance (TEER) of the cell monolayer was measured every day to indicate the formation of hCMEC/D3 monolayers. When TEER value reached 50 Ω cm −2 and remained stable (Figure S5, Supporting Information), [ 31 ] various C6‐loading preparations were added in the upper chamber. To evaluate BBB permeability and cellular internalization, fluorescence images of BV‐2 cells on the lower chamber were visualized under inverted fluorescence microscope.…”
Section: Resultsmentioning
confidence: 99%
“…The main challenge in treating glioma is BBB permeation and delivery of anticancer drug at the therapeutic dose to the tumour (Islam et al., 2021; Pardridge, 2007). Nonspecific cytotoxicity, poor biocompatibility and low delivery efficiency have been reported in the traditional nano‐delivery systems (Thomas et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Delivery to central nervous system faces challenges posed by blood‐brain barrier (BBB). [ 15 , 16 , 17 , 18 ] A recent study showed, only about 1% of nanocarriers can accumulate with high permeability and retention in xenografted tumors; this low rate is possibly due to multiple physiological barriers. [ 19 , 20 ] These challenges indicate that the nanocarriers must be substantially improved.…”
Section: Introductionmentioning
confidence: 99%